Comparison between ELISA and ICT- MycoDot in adult pulmonary tuberculosis - Shamsuzzaman, AK; Akhter, S; Shamsuzzaman, SM; Siddique, A (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):33-9 The abstract of this article is available on the PubMed website